The Impact of Abdullah Avlani’s Literary Work on Youth Development (Eurasian Journal of Learning and Academic Teaching, 2024)
Тhis article is about Abdulla Avlani, who has a place in the history of Uzbek pedagogy, has written a lot of scientific works and books about child education and its features. The main content of the article is the use and application of the literature left by Avlani in educational science.